Egyptian cultural identity in the architecture of Roman Egypt (30 BC-AD 325) - Abdelwahed, Youssri Ezzat Hussein. (Oxford)
x, 222 sayfa
Keywords: “This volume considers the relationship between architectural form and different layers of identity assertion in Roman Egypt. It stresses the sophistication of the concept of identity, and the complex yet close association between architecture and identity. Egyptian Cultural Identity in the Architecture of Roman Egypt (30 BC-AD 325) considers the relationship between architectural form and different layers of identity assertion in Roman Egypt. The Roman province of Aegyptus was a peculiar province such that many scholars have generally assumed that it was given a special status in the Roman Empire. The text covers the period from the Roman conquest of Egypt under Octavian in 30 BC to the official recognition of Christianity in AD 325. It stresses the sophistication of the concept of identity, and the complex yet close association between architecture and identity. This monograph is the outcome of four years of research at the Department of Classics and Ancient History, the University of Durham. The book will be of interest and value for both Classicists and Egyptologists working on the archaeology of Egypt under Roman rule and the concept of identity.” --